2009
DOI: 10.1038/ncb1849
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent regulation of cytosolic localization and oncogenic function of Skp2 by Akt/PKB

Abstract: Skp2 is an F-box protein that forms the SCF complex with Skp1 and Cullin-1 to constitute an E3 ligase for ubiquitylation. Ubiquitylation and degradation of the p27 is critical for Skp2-mediated cell cycle entry, and overexpression and cytosolic accumulation of Skp2 have been clearly associated with tumorigenesis although the functional significance of the latter has remained elusive. Here we show that the Akt/PKB interacts with and directly phosphorylates Skp2. We find that Skp2 phosphorylation by Akt triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
263
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(292 citation statements)
references
References 42 publications
24
263
4
1
Order By: Relevance
“…For example, Skp2/Fbxl1 localization is controlled by phosphorylation. It has been shown that phosphorylation of Skp2/Fbxl1 at Ser-72 during M phase may trigger its export to the cytoplasm affecting its ability to form functional SCF complexes (5,6). However, these observations remain controversial (7,8).…”
mentioning
confidence: 83%
“…For example, Skp2/Fbxl1 localization is controlled by phosphorylation. It has been shown that phosphorylation of Skp2/Fbxl1 at Ser-72 during M phase may trigger its export to the cytoplasm affecting its ability to form functional SCF complexes (5,6). However, these observations remain controversial (7,8).…”
mentioning
confidence: 83%
“…Reduced HBx expression results in enhanced susceptibility of cells to anticancer drugs and induced proliferation suppression and apoptosis (28). HBx can increase SMYD3 expression, and SMYD3 upregulates c-myc in hepatoma; therefore we suggest that SMYD3-c-myc might be one of most important pathways in the development and progression of HBx-related HCC (29). HBx also plays a role in regulating a series of cell-signaling cascades, most notably in the Ras-and Raf-induced mitogen-activated protein kinase pathways, and in inactivation of tumor suppressive genes through promoter hypermethylation (30).…”
Section: Discussionmentioning
confidence: 99%
“…The SCF Skp2 complex is under tight bimodal regulation by the concerted actions of various kinases that modulate its activity by phosphorylating either its components (19,22,33) or its target proteins (26). Since there is compelling evidence for the requirement of substrate phosphorylation as a signal for SCF Skp2 -mediated protein turnover (57, 58), we have investigated the role of such posttranslational modifications in Skp2-mediated ER␣ turnover and identify the stress-activated kinase p38MAPK as a critical regulator.…”
mentioning
confidence: 99%